PENERAPAN WEB SCRAPING DESKRIPSI PRODUK MENGGUNAKAN SELENIUM PYTHON DAN FRAMEWORK LARAVEL - Stephen Kusumo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The development of buying and selling goods on the online market can affect the development of electronic commerce (E-Commerce). Many E-Commerce sites offer products with different prices and descriptions. Limitations time in managing product data can be overcome by using a web scraping process. Web scraping is the process of retrieving a semi-structured document from the internet with the aim of retrieving data or information in whole or in part from a page in the form of a website with a markup language such as HTML or XHTML for other purposes. of course will spend a lot of time if you have a lot of product data. With these problems, a system design using selenium python and the laravel framework was carried out to retrieve data and edit data to be more efficient in managing product data. The result of the application of web scraping is that users can retrieve information data in the form of product descriptions quickly and accurately on e-commerce sites and e-marketplaces, namely Shopee using MySQL database storage.